Responsive units: Behavioral elements for coordination-oriented development of object-oriented systems. - Dumitru, Teodor. (University of Ottawa (Canada), 2000)
Theoretically, the thesis sustains that in object oriented systems---mainly event driven---(1) the dialog between objects is essential, (2) the dialog implies coordination, (3) a dialog coordination object---that separates coordination from activities---is useful for response design. Practically, it is proposed a design modality based on Responsive Units. It is a model which directly captures the logic of interactions between objects, without much overhead. The approach is an extension (adaptation) of 'Coordination Oriented Design' (COD) towards object orientation. It uses the basic principle of COD of separating coordination from execution. We address the problem that in OO systems, even mono-threaded, the event responses can be only partially defined. This mainly happens because interaction diagrams can capture only a few interaction sequences and because object implementation hardly relates to their behavioral design. An improvement in the definition of event responses would be beneficial, mainly for systems in which the sequence of interactions is complicate to design, but critical. (Abstract shortened by UMI.)
Keywords: Engineering, Electronics and Electrical.